PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA PADA BANK DI KOTA MERAUKE - Funnisia Lamalewa (Universitas Musamus,Merauke,Papua, 2015)
As benefits an organization, one of the strategic functions play an important role in banking is its human resources. This aim of the research was to find out the significant influence of compensation and job satisfaction on employee performance through job motivation, either directly or indirectly. The objectof the research were bank employees in Merauke City. The data consisted of primary data obtained using questionnaire give to respondents related to compensation, job satisfaction, motivation and performance of employees. The data were analyzed using quantitative approach through path analysis to test the hypothesis. The results of the research indicate that (1) compensation and job satisfaction have a positive and significant influence on job motivation, (2) compensation and job satisfaction have a positive and significant influence on employees performance. (3) compensation indirectly has a positive and significant influence on employees performance through job motivation, and (4) job satisfaction indirectly has a positive and significant influence on employess performance through job motivation of bank employees' in Merauke City.